Playing to the Gallery: The Impact of Courtroom Performance on the Sentences Received by Convicted Terrorists in the UK and France - Copeland, Simon (Perspectives on terrorism, 2024)
Terrorism trials, particularly those that address events of national significance, are performative spaces. As such, these proceedings carry a risk of becoming public spectacles. Aside from trying to ‘win’ the trial in a legal sense, the various parties involved may use the courtroom to present narratives about justice and injustice, the legitimacy of a political or ideological cause, or even attempt to undermine the judicial process entirely. Conversely, terrorist suspects often deploy established performative templates in the hope of receiving a shorter prison sentence, in particular, by demonstrating remorse for their actions. Despite this, our understanding of the impact of the ‘theatre’ of terrorism trials is limited, with existing analysis focusing largely on the reception of different performances and narratives by audiences outside the courtroom, namely the media and the public. This article examines how the conduct of these proceedings and the ‘performative strategies’ of the parties involved impact the sentences handed down by the judge as a result of a guilty verdict. Focusing on the UK and France, it interrogates the sentences received by guilty defendants in several high-profile terrorism cases. Included is an examination of the ‘absent presence’ of defendants who are tried in absentia and the impact this nonappearance might have upon sentencing. Analysing their sentencing remarks, it also evaluates how judges interpret, account for, and present these factors as part of their decision-making processes.